Lumbar Drain Tunneling: A Safe Two-Needle Technique - Deepti, Srinivas; Ashwini, Halesh; Venkatesh, Keshavan (Journal of Neuroanaesthesiology and Critical Care, 2019)
Lumbar drain catheter insertion for prolonged periods of time is necessary in a myriad of neurosurgical patients which entails its tunneling. We describe a safe and simple technique of catheter insertion and tunneling using two Tuohy needles instead of one, which prevents unintentional catheter damage during the procedure.
Keywords: lumbar drain; lumbar drain tunneling; Tuohy needle